DEVELOPMENT FEATURES OF THE UKRAINIAN STOCK MARKET AS A COMPONENT OF STATE FINANCIAL SECURITY - FROLOV, Serhiy; ORLOV, Volodymyr; DYKHA, Mariia (Scientific journal «World of Finance», 2022)
Introduction. Peculiarities of functioning and structure of the stock market of Ukraine play an important role in ensuring the state economic security and, in particular, financial. The purpose of the article is to analyze the state and features of the modern stock market of Ukraine, to investigate its impact on the state of financial security of the country. Results. Imbalances in the primary securities market are due to the small number and volume of issues, as well as the predominance of issuers of state banking institutions and state corporations, which carried out the issue to keep banks at the required level of capital and replenishment. The volume and number of bond issues are significantly lower compared to stocks. There are currently four exchanges in Ukraine, but primary stock market operations are focused on the PFTS. The secondary securities market of Ukraine is more developed in Ukraine (the total amount of transactions is more than 90% of the volume of exchange contracts during the entire analyzed period). Transactions are carried out mainly on stock exchanges – PFTS and “Perspective”. The trend of the results of the secondary stock market has improved (significantly decreases the value of indicators – linear deviation, variance, oscillation coefficient), however, the value of the oscillation coefficient still indicates a lack of homogeneous and balanced environment. Approximations to the state of homogeneity can be characterized by stock exchange contracts concluded on government bonds. At the same time, the volume of concluding exchange contracts is generally insignificant, and the share of exchange contracts on government bonds in total is approaching almost 100%; therefore, it can be concluded that the entire stock market is characterized by significant heterogeneity and imbalance. Conclusions. The stock market of Ukraine does not fulfill its key function – investment. The stock market of Ukraine is characterized by pronounced imbalances. At the same time, it should be emphasized that the structure of the stock market is characterized by dynamic processes, so the creation of a fully balanced environment can not be a priority. The stock market of Ukraine mostly serves the needs of the public sector of the economy and in no way contributes to the development of not only the real but also the financial sector of the economy. That is, the security of the stock market is directly related to the security of debt and budget, which are components of the financial security of the state.